Studying The Physical And Mechanical Properties Of Roller Compacted Concrete Used In The Construction Of Gravity Dams - منذر حماد; علي خيربك; علي فيصل بليدي (Latakia University Journal -Engineering Sciences Series, 2023)
Roller Compacted Concrete (RCC) is usually used in paving roads and airports and building block structures as a result of its quality represented by high strength , speed of implementation and low construction cost. In order to reduce the amount of building materials (portland cement) thus achieving economic savings, the tendency was to use Roller Compacted Concrete RCC to build gravity dams, several concrete mixtures have been designed with local materials and inexpensive additives (marble powder), which are used as a substitute for fly ash and natural pozzolan, which are commonly used in building RCC dams. In this research, the physical and mechanical properties of the produced concrete were studied, and we reached a mixture using low quantity cement 150 kg/m3, which achieved a high density 2540 Kg/m3 and compressive strength 14.6 MPa, which is very good for the requirements of concrete used in dams, as well as achieving direct tensile strength 1.56 MPa and impermeability to water penetration.